Gambaran Tingkat Atensi Pasien Stroke Pasca Mengalami Serangan Berulang - Ni Luh Putu Thrisna Dewi; Ni Made Nopita Wati; Ketut Lisnawati; Ni Ketut Ayu Mirayanti (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
Stroke causes several physical and psychological symptoms. Early strokescontribute to a very significant risk of recurrent attacks. If there iscognitive impairment, it can affect one of the cognitive functions such asattention. This study aims to determine the description of the level of attentionof stroke patients after experiencing repeated attacks. The method and design ofthis study were a descriptive study using frequency distribution, with a cross-sectionalÂ research approach. The samples were 67 post-stroke patients whoexperienced repeated attacks, using non-probability sampling techniques withpurposive sampling techniques based on inclusion and exclusion criteria anddata collection using the TMT (trail making test A and B) questionnaire. Theresults of this study describe that most of the respondents have less attention inthe category of 56 people (83, 6%). Factors that can affect attention are age, theolder a person gets, the worse his or her attention after a stroke is coupled withthe degenerative process experienced by stroke sufferers. Prolonged stressand psychological conditions and the inability to adapt to new conditions greatlyinterfere with the recovery process because on average stroke patients not onlyexperience sequelae after an attack but also unstable psychological conditionsthat can worsen their physical condition. Conclusions: Identification respondents'attention has a poor attention category mostly, it is necessary to carry outpreventive, curative, or rehabilitative promotive prevention in stroke patients bymodifying a healthy lifestyle to prevent recurrent attacks